Definitions and Theoretical Approximations to the Travel Literature Genre - González Otero, Angélica (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This reflection article makes a theoretical journey through the genre of travel literature; in order to present its different historical and sociocultural perspectives, as well as different ways of reading this genre from critical literary theory. Similarly, this article inquires into the importance of the genre in Latin American literature, its historical evolution and its contribution to the construction of memory and identity in the continent.